Crying as a precipitating factor for migraine and tension-type headache - Fragoso, Yara Dadalti; Carvalho, Regina; Ferrero, Fernanda; Lourenço, Darcya Maria; Paulino, Erica Regina (São Paulo Medical Journal, 2003)
CONTEXT: Scarcely reported in the literature, crying seems to be an important precipitating factor for both migraine and tension-type headache in daily practice. OBJECTIVE: To evaluate the role of crying as a precipitating factor for migraine and tension-type headache. TYPE OF STUDY: Prospective evaluation. PARTICIPANTS: 163 workers or students from the Universidade Metropolitana de Santos, who presented at least one attack a month, for at least one year, of either migraine or tension-type headache. PROCEDURES: Interview by means of questionnaires and personal evaluations. Details of precipitating factors for the attacks were assessed. RESULTS: From the total group of 163 individuals, 90 (55.2%) considered crying to be a potential factor for triggering headache attacks. Of this group of 90 persons, 62 presented migraine (6 males, 56 females) and 28 presented tension-type headache (5 males, 23 females). Only stress, anxiety and menstrual periods rated higher or equal to crying as triggering factors for both types of headache. CONCLUSIONS: The physiology of crying is not well documented or understood. The act of crying seems to be an important precipitating factor for primary headaches and it should be studied further. The authors welcome comments on the matter and would like to work in collaboration with other groups interested in this subject.